PEMBENTUKAN KARAKTER KEPEMIMPINAN PEMUDA MELALUI WADAH PEMBINAAN DEWAN KERJA PRAMUKA PENEGAK DAN PRAMUKA PANDEGA DI KWARTIR CABANG KUDUS - Sulaswari, Misroh; Yaqin, Muhammad Nurul; Hafidz, Muhammad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2020)
This character research takes the object of guiding rover scout and ranger scout in shaping the leadership character of its organizational members. The process of conducting this research will use descriptive qualitative methods to produce the reality of the characters formed in the scout formation for rover scout and ranger scout in Kudus. Investigation of researchers used interview and observation techniques whose results showed a significant influence on the leadership character of the members of the holy branch work council. The form of responsibility and the five-year mandate entailed from the Musppanitra session had a role in shaping the character. Not only that, the process of dynamics for five years there are goals that are social oriented and not Profit oriented to make the work sincere and complete.